The Effectiveness of Written Arabic Method Based on Contextual Learning on Arabic Education Student at The Islamic Institute of Jember - Bambang Irawan (Universitas Yudharta Pasuruan, 2020)
Over several years, the researcher noted that the students in the Arabic Education of State Islamic Institute of Jember were bored with teaching and learning writing skills, and the competence of this skill is low. This research aims to: (1) produce a module in Arabic Writing Teaching Based on The Contextual Teaching Learning that called